Biosensors for amplification-free viral RNA detection - Parassol, Brenda G.; Kusimoto Takeuti, Nayla Naomi; Faria, Henrique Antonio Mendonça [UNESP]; Jorge, Kelly C.; Sampaio, Isabella; Zucolotto, Valtencir; Vieira, Nirton C.S. (Elsevier, 2024)
Viruses are infectious agents that cause various diseases worldwide. The recent COVID-19 pandemic has shown the need for rapid and reliable tests to confirm viral infections, aiming at the rapid isolation, treatment, and identification of high-incidence regions. Rapid antigen tests based on lateral flow immunochromatography have proven to be very useful. However, they are not accurate in patients with low viral loadings. The gold standard test is RT-PCR, which identifies parts of the viral genome by detecting specific DNA or RNA sequences. RT-PCR or similar tests such as RT-LAMP involve several steps for sample preparation and amplification of target sequences, require trained personnel to be performed, and can be time-consuming and expensive, limiting their point-of-care application. Biosensors are promising analytical devices for detecting nucleic acids, mainly RNA from viruses, offering advantages such as rapid results, high sensitivity, and low cost compared with the RT-PCR test since the amplification of target sequences is not necessary. Recently, several biosensors have been developed to detect RNA viruses without sequence amplification. Here, we present a review on the design and technology of amplification-free biosensors for the detection of viral RNA as an alternative for diagnosing infectious diseases. The challenges and advances for the point-of-care electrochemical, electrical, and optical biosensors will be addressed.
Keywords: Amplification-free; Biosensors; Diagnosis; RNA; Viruses